2021
DOI: 10.1136/bcr-2021-244830
|View full text |Cite
|
Sign up to set email alerts
|

Wall eyed bilateral internuclear ophthalmoplegia (WEBINO) syndrome as a false localising sign in intracranial haemorrhage due to snake bite

Abstract: A 48-year-old woman presented with sudden-onset altered sensorium 2 days after a snake bite (unidentified species) and was found to have a large right frontal intracerebral haemorrhage (ICH) with transtentorial herniation (TTH) causing brain stem compression. A day later, neurological examination revealed internuclear ophthalmoplegia (INO) fitting the clinical description of wall eyed bilateral INO syndrome. INO is a rare ocular motor sign, the most common causes being brain stem infarction, haemorrhage or dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Studies have shown that the disease is often associated with brainstem ischemia and hydrocephalus, immunotherapy of tumors, and diseases such as multiple sclerosis. This study summarized 39 case reports, including 42 WEBINO patients (Inocencio and Ballecer, 1985;Lana et al, 1990;Fay and Strominger, 1999;Korkmaz et al, 2002;Ozer et al, 2005;Chen and Lin, 2007;Kim et al, 2008;Matsumoto et al, 2008Matsumoto et al, , 2019Ushio et al, 2008;Jacob et al, 2010;Sierra-Hidalgo et al, 2010;Shinoda et al, 2011;Beh and Frohman, 2012;Jadhav and Prasad, 2012;Sakamoto et al, 2012;Bar et al, 2014;Chakravarthi et al, 2014;de Mora et al, 2014;Mathis et al, 2014;Muralidhar et al, 2014;Nakajima et al, 2014;Toufeeq and Dave, 2014;Agarwal et al, 2015;Ljevak et al, 2015;Man et al, 2015;de Souza et al, 2017;Sajjadi et al, 2017;Zou and Chen, 2017;Keereman et al, 2018;Papageorgiou et al, 2018;Im et al, 2020;Vázquez-Justes et al, 2020;Yazdi et al, 2020;Ansari et al, 2021;Jo et al, 2021;Petrik et al, 2021;Sinha et al, 2021;Wako et al, 2022). The age range of the ...…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the disease is often associated with brainstem ischemia and hydrocephalus, immunotherapy of tumors, and diseases such as multiple sclerosis. This study summarized 39 case reports, including 42 WEBINO patients (Inocencio and Ballecer, 1985;Lana et al, 1990;Fay and Strominger, 1999;Korkmaz et al, 2002;Ozer et al, 2005;Chen and Lin, 2007;Kim et al, 2008;Matsumoto et al, 2008Matsumoto et al, , 2019Ushio et al, 2008;Jacob et al, 2010;Sierra-Hidalgo et al, 2010;Shinoda et al, 2011;Beh and Frohman, 2012;Jadhav and Prasad, 2012;Sakamoto et al, 2012;Bar et al, 2014;Chakravarthi et al, 2014;de Mora et al, 2014;Mathis et al, 2014;Muralidhar et al, 2014;Nakajima et al, 2014;Toufeeq and Dave, 2014;Agarwal et al, 2015;Ljevak et al, 2015;Man et al, 2015;de Souza et al, 2017;Sajjadi et al, 2017;Zou and Chen, 2017;Keereman et al, 2018;Papageorgiou et al, 2018;Im et al, 2020;Vázquez-Justes et al, 2020;Yazdi et al, 2020;Ansari et al, 2021;Jo et al, 2021;Petrik et al, 2021;Sinha et al, 2021;Wako et al, 2022). The age range of the ...…”
Section: Discussionmentioning
confidence: 99%
“…However, multiple small cerebral hemorrhages occurred on the morning of day 6; on day 7 he passed away. A 48-year-old woman in India was bitten by an unidentified snake and was diagnosed with intracranial hemorrhage and exotropia in the hospital [ 20 ]. She received AV treatment and transfusion of fresh frozen plasma to correct the suspected venom-induced consumptive coagulopathy.…”
Section: Brain Complicationsmentioning
confidence: 99%
“…The venom will induce a loss of strength due to a blockage in nerve communication. An eye movement abnormality and palpebral ptosis (drooping of the eyelids) are two of the early indications of paralysis [11]. A diverse variety of compounds and phytochemicals are produced by plants [12].…”
Section: Introductionmentioning
confidence: 99%